Fetal neurosonography at 31–35 weeks reveals altered cortical development in pre‐eclampsia with and without small‐for‐gestational‐age fetus. (13th May 2022) - Basso, A.; Youssef, L.; Nakaki, A.; Paules, C.; Miranda, J.; Casu, G.; Salazar, L.; Gratacos, E.; Eixarch, E.; Crispi, F.; Crovetto, F.
ABSTRACT: Objective: To explore the pattern of fetal cortical development in pregnancies complicated by pre‐eclampsia (PE), with and without a small‐for‐gestational‐age (SGA) fetus, compared to uncomplicated pregnancies. Methods: This was a prospective observational study including singleton pregnancies complicated by normotensive SGA (birth weight < 10 th centile) ( n = 77), PE with an appropriate‐for‐gestational‐age (AGA) fetus ( n = 76) or PE with a SGA fetus ( n = 67), and 128 uncomplicated pregnancies (normotensive AGA) matched by gestational age at ultrasound. All pregnancies underwent detailed neurosonography, using a transabdominal and transvaginal approach, at 31–35 weeks' gestation to assess the depth of the insula, Sylvian fissure, parieto‐occipital sulcus, cingulate sulcus and calcarine sulcus. All measurements were adjusted for biparietal diameter (BPD). In addition, a grading score of cortical development was assigned to each brain structure, ranging from Grade 0 (no development) to Grade 5 (maximum development). Univariate and multiple regression analyses were conducted. Results: Similar to findings in previous studies, normotensive pregnancies with a SGA fetus showed significant differences in cortical development compared with controls, with reduced Sylvian fissure depth adjusted for BPD (14.5 ± 2.4 vs 16.6 ± 2.3; P < 0.001) and increased insula depth adjusted for BPD (33.2 ± 2.0 vs 31.8 ± 2.0; P < 0.001). Interestingly, a similar cortical development pattern was observed in PE pregnancies with a SGA fetus and in PE pregnancies with an AGA fetus, manifested by reduced Sylvian fissure depth adjusted for BPD (14.2 ± 2.3 and 14.3 ± 2.3 vs 16.6 ± 2.3; P < 0.001 for both) and greater insula depth adjusted for BPD (33.2 ± 2.1 and 32.8 ± 1.7 vs 31.8 ± 2.0; P < 0.001 for both) compared with controls. No significant differences were observed in parieto‐occipital, cingulate sulcus or calcarine sulcus depth across the study groups. The Sylvian fissure was scored as Grade 4 in significantly more (93.2% vs 59.5%) and as Grade 5 in significantly fewer (2.7% vs 37.3%) PE pregnancies with an AGA fetus compared with controls ( P < 0.05 for both). These differences remained significant even after statistical adjustment for potential confounders, including ethnicity, low socioeconomic status, nulliparity, chronic hypertension, pregestational diabetes, assisted reproductive technologies, smoking and fetal gender, with the application of Benjamini–Hochberg procedure for multiple comparisons. Conclusions: PE with or without SGA is associated with a differential fetal cortical development pattern which is similar to that described previously in small fetuses. Future research is warranted to elucidate better the mechanism(s) underlying these changes. © 2022 International Society of Ultrasound in Obstetrics and Gynecology.